Satisfaction of imaging report rendered in emergency setting: a survey of radiology and referring physicians - Manoonchai, Naree; Kaewlai, Rathachai; Wibulpolprasert, Arrug; Boonpramarn, Ugrit; Tohmee, Adul; Phongkitkarun, Sith (Academic radiology, 2015)
To determine physicians' preference toward three types of structured imaging reports (basic structured report [BSR], itemized report [IR], and point-and-click report [PCR]) used in emergency radiology. Survey questions were created and considered valid and reliable based on index of item objective congruence from three specialists (>0.75) and a pilot of 25 subjects (Cronbach alpha, 0.83-1.00). Respondents included trainees and attendings in radiology and referring physicians working in the academic emergency department at the time of survey rollout. They were provided report examples of each type and asked to complete a questionnaire consisting of the following five parts: demographics, necessity of imaging report, report quality (content, format and organization, and language), process of reporting, and components of imaging report. For rating scores, the higher value means the higher preference and agreement. The survey received 79.5% response rate. Respondents included 101 physicians (mean age, 29.4 years; 61 radiology physicians and 40 referring physicians; 81 trainees and 20 attending). Overall, IR was preferred over PCR and BSR by all physicians with scores (out of 10) as follows: IR, 7.62-8.83; PCR, 6.62-8.55; BSR, 5.23-6.65; P < .001. IR received scores (out of 5) of 4.03-4.37, PCR 3.32-4.52, and BSR 2.59-3.86 for report quality. For process of reporting, IR had scores (out of 5) of 3.80-4.56, PCR 2.79-4.09, and BSR 2.32-3.56. In emergency setting, physicians preferred IR over PCR and BSR. IR and PCR were equal in report quality metrics, but IR was most preferred in the process of reporting. BSR ranked last in both quality and process.